Framework of the Mediation Effect of Artificial Intelligence Usage on the Relationship Between Innovation Factors and Organisational Performance - Shamma Ebraheem Esmaeel Saleh Alhosani; Edie Ezwan Mohd Safian (International Journal of Sustainable Construction Engineering and Technology, 2024)
This paper details a study focused on establishing a framework to examine how Artificial Intelligence Usage mediates the relationship between innovation factors and organizational performance. Before constructing the framework, a Partial Least Squares Structural Equation Modelling (PLS-SEM) mediation model was formulated using SmartPLS software. This model encompasses innovation factors categorized into three groups: marketing, management, and process, treated as independent constructs, while organizational performance serves as the dependent construct, with artificial intelligence usage acting as the mediator. Data for constructing the model were gathered through a questionnaire survey administered to 129 employees of ADNOC, selected via convenient random sampling. The constructed model underwent rigorous assessment of its inner and outer components until meeting predefined fitness criteria. Subsequently, a bootstrapping procedure was employed for hypothesis testing to ascertain the significance level of each relationship path, facilitating the determination of mediation effects. The framework emerged from the results of these mediation effects, indicating that process innovation achieved partial mediation, management innovation achieved full mediation, while marketing innovation showed no mediation effect. This framework is poised to aid ADNOC employees in integrating innovation factors with artificial intelligence usage to enhance organizational performance.